PERAN IBU DALAM MEMENUHI KEBUTUHAN GIZI SEIMBANG BATITA DI DUSUN BUNGKEM DESA KWEDEN KEMBAR KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Indatul Laili, Siti; Wulandari, Yani (JURNAL KEPERAWATAN SEHAT, 2015)
The golden age was a time of growth and development at this age is a period of rapid and never repeated, which of children age 1 – 3 years should be given food with balanced nutrition. So that mothers play an important role in providing balanced nutrition for toddlers. The purpose of this research was to determine the role of the mother in meeting the nutritional needs of toddlers in the village, by village Bungkem, Kweden Kembar, Mojoanyar, Mojokerto district. The research design used is descriptive. The sampel is in getting as many as people who have decision criteria for inclusion with purposive sampling teckhnic. The data was taken using a questionnaire cantaining 20 question. Research result in as many as 11 people get a percentage of 55% with a negative role in education because of poor factor. Good mothers who have little education and are well educated in the expected increase understanding or searching for information about nutritional requirements needed by toodlers throught counseling at the time of early childhood facilities in the local authorities so as to address the role of the mother is negative and can improve child nutrition.Keywords: Roles, Toodlers, Nutritional needs.